2012
DOI: 10.1021/jf300460g
|View full text |Cite
|
Sign up to set email alerts
|

Steam-Dried Ginseng Berry Fermented with Lactobacillus plantarum Controls the Increase of Blood Glucose and Body Weight in Type 2 Obese Diabeticdb/dbMice

Abstract: This study examined whether steam-dried ginseng berries fermented with Lactobacillus plantarum (FSGB) could improve the indices of type 2 diabetes mellitus (T2DM) in obese db/db mice. FSGB was shown to have an effect on body weight and blood glucose/serum parameters when administered at a dose of 0.5 g/kg. In the intraperitoneal glucose tolerance test (IPGTT) and insulin tolerance test (ITT), FSGB was clearly shown to improve insulin tolerance and glucose tolerance. Moreover, FSGB was shown to enhance immune a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 36 publications
1
13
0
Order By: Relevance
“…FSGB improved insulin and glucose tolerance levels. It also enhanced immune activities by increasing immune cell population and glucose transporter 1 (GLUT1) mRNA expression in L6 cells was up-regulated, showing that FSGB may increase glucose activity transport to target cells.[68] Lactobacillus acidophilus La5Probiotic yogurt consumption caused a 4.54% decrease in total cholesterol and a 7.45% decrease in LDL-C compared with the control group. Total cholesterol level (HDL-C ratio and LDL-C:HDL-C ratio) significantly decreased in the probiotic group compared to the control[69] Bifidobacterium lactis Bb12 Bifidobacterium animalis subsp.…”
Section: Probiotic Lab and Type-2 Diabetes Treatmentmentioning
confidence: 99%
“…FSGB improved insulin and glucose tolerance levels. It also enhanced immune activities by increasing immune cell population and glucose transporter 1 (GLUT1) mRNA expression in L6 cells was up-regulated, showing that FSGB may increase glucose activity transport to target cells.[68] Lactobacillus acidophilus La5Probiotic yogurt consumption caused a 4.54% decrease in total cholesterol and a 7.45% decrease in LDL-C compared with the control group. Total cholesterol level (HDL-C ratio and LDL-C:HDL-C ratio) significantly decreased in the probiotic group compared to the control[69] Bifidobacterium lactis Bb12 Bifidobacterium animalis subsp.…”
Section: Probiotic Lab and Type-2 Diabetes Treatmentmentioning
confidence: 99%
“…One other study was excluded as it reported the same outcomes published previously in line with other new but irrelevant results [38]. Six other studies were excluded as they evaluated the effects of synbiotics [39][40][41][42][43] or prebiotics [44]. Three animal reports that were published in languages other than English were excluded as well [45][46][47].…”
Section: Probiotics and Diabetesmentioning
confidence: 99%
“…Similar results were also observed in db/db mice treated with ginseng extracts. 0.5 g/kg fermented steam-dried ginseng berry (FSGB) [45] significantly decreased body weight and blood glucose in db/db mice during a 35-day treatment; furthermore, the plasma insulin in the FSGB treated group (17.05 ± 0.49 ng/mL) significantly increased almost double compared to the untreated db/db group (8.21 ± 0.60 ng/mL). GLUT1 mRNA expression was up-regulated by FSGB in the L6 skeletal muscle cells.…”
Section: Potential Mechanisms Of the Anti-diabetic Effect Of Ginsengmentioning
confidence: 99%